Incidence and Related Factors for Hospital-Acquired Pneumonia Among Older Bedridden Patients in China: A Hospital-Based Multicenter Registry Data Based Study - Jiao, Jing; Yang, Xiang-yun; Li, Zhen; Zhao, Yan-wei; Cao, Jing; Li, Fang-fang; Liu, Ying; Liu, Ge; Song, Bao-yun; Jin, Jing-fen; Liu, Yi-lan; Wen, Xian-xiu; et al. (Frontiers in Public Health, 2019)
Objective: To identify the incidence and related factors for hospital-acquired pneumonia (HAP) among older bedridden patients in China. Study design and setting: This multicenter registry data- based study conducted between September 2015 and March 2016 surveyed 7324 older bedridden patients from 25 hospitals in China (six tertiary, 12 non-tertiary and seven community hospitals). The occurrence of HAP among all participants was monitored by trained investigators. Demographics, hospitalization information and comorbidity differences were compared between patients with and without HAP. A multilevel regression analysis was used to explore the factors associated with HAP. Results: Among 7324 older bedridden patients, 566 patients were diagnosed with HAP. The incidence of HAP in this study was 13.9 per 1000 person-days. There were statistical differences in gender, age, length of bedridden days, BMI, smoking, department, undergoing general anesthesia surgery, ventilator application, Charlson comorbity index (CCI) score, disturbance of consciousness, tranquilizer use, glucocorticosteroid use and antibiotic use between patients with HAP and patients without HAP (all p < 0.05). Multilevel regression analysis found no significant variance for HAP at the hospital level (0.332, t = 1.875, p > 0.05). There were significant differences for the occurrence of HAP among different departments (0.553, t = 4.320, p < 0.01). The incidence density of HAP was highest in the ICU (30.1 ‰) among the selected departments, followed by the departments of neurosurgery (18.7 ‰) and neurology medicine (16.6 ‰). Individual patient -level factors, including older age, disturbance of consciousness, total CCI score, ICU admission, and glucocorticoid and antibiotic use, were found to be associated with the occurrence of HAP (all p < 0.05). Conclusion: A relatively high incidence density of HAP among older bedridden patients was identified, as well as several factors associated with HAP among the population. This suggests that attention should be paid to the effective management of these related factors of older bedridden patients to reduce the occurrence of HAP.